Location domination number of line graph. (4th July 2019) - Rajasekar, G.; Nagarajan, K.
Abstract: A set S which dominate and uniquely locate all vertices in the set V ( G ) – S is a locating dominating set. In this paper location domination number of line graph of Pn, Cn, Sn, Bm, n, F 1, n and Wn have been found